TASKA Teachers' Perception of PERMATA Early Childhood Nursing and Education Course Certification - Nuzha Mohamed Taha, Sharina Abu Bakar, Prof. Dr. Putri Zabariah Megat A.Rahman, Izawati Ngadni, Siti Amira Baharuddin (Mathematical Statistician and Engineering Applications, 2023)
TASKA teachers in childcare centres or TASKA play a very important role in shaping children's foundation, including the aspects of personality, knowledge, and worldview. TASKA teachers are not only responsible for taking care of children but also for influencing the children on the basics of life and education. In Malaysia, to be certified as a TASKA teacher, the candidate must fulfill the minimum eligibility requirement, which is earning the Kursus Asuhan PERMATA (KAP) certificate. This qualitative study explores TASKA teachers' perception of KAP certification as the minimum requirement to qualify as registered teachers and certified by Jabatan Kebajikan Masyarakat (JKM). This survey involved four teachers from several registered TASKA at Bandar Baru Bangi. The data collection method involved interviews, observation, field notes, and document analysis. The finding indicates that KAP certification benefits TASKA teachers and equips them with basic knowledge in early childhood education. KAP certification also helps teachers to understand their roles and responsibilities in nurturing children during their precious ages.